The Business Strategy Analysis of Netflix - Hsiao, Yu-Hao (Transactions on Social Science, Education and Humanities Research, 2024)
Netflix has undergone some actual revolution since its founding in 1997. This article introduces the way the strategic development of Netflix has turned it into a giant of streaming services from a simple form for renting DVDs. Utilizing a variety of theoretical frameworks and industry analyses, the paper analyzes Netflix’s subscription-driven revenue model, innovation in original content investments, globalization efforts, and technology-driven innovation. The paper will discuss the international expansion strategy of Netflix, involving the need for localization of content and acquisition of content at the entrance of the company in the foreign market, and further appraises technological innovations at Netflix, such as AI and machine learning, VR and AR, and how they contribute to improvements in service outcomes and enhancements in engagement. The Personalization and recommendation technologies could be technologically advanced in enabling Netflix to become personal in its recommendations and, consequently, give an immersive entertainment experience, all from a global audience. In such a course, Netflix has seen unseemly success so far; nevertheless, some challenges remain. Content cost pressures, competition from foreign and domestic rivals, and consumers changing their preferences are to name a few. International expansion, diversification of content offerings, and partnership with the same business lie in growth and innovation paths. In this respect, Netflix will emerge as the preeminent player in the dynamic ecosystem of the entertainment industry by exploiting sustainability, adaptability, and innovation.